An Important Risk to Prevent in the Operating Room: Pressure Injury - Sema Konateke (Atatürk University, 2021)
Pressure injury is a global problem that needs to be prevented and treated, as it significantly increases healthcare costs, requires a long treatment process and prolongs hospital stay. Pressure injury negatively affect the quality of life by causing pain, social isolation and job losses. Surgery is an important risk for pressure injury. Pressure injuries that develop within the first 48-72 hours after surgery are considered to be due to surgery. Exposure of the patient to pressure and friction force in carrying or positioning procedures, prolongation of the operation time depending on the type of surgery, deterioration of sensory perception with the effect of anesthesia are the risk factors that cause pressure injury during surgery. In addition, individual specific risk factors also increase the risk of pressure injury due to surgery. Low or high body mass index, advanced age, comorbid diseases are individual risk factors that should be evaluated before surgery. Evidence-based guidelines for the prevention of pressure injuries due to surgery; it recommends performing perioperative pressure wound risk assessment, repositioning the patient, using support surfaces cutting off the contact of the heels with the operating table, and distributing the pressure evenly throughout the body. Operating room nurses, who are an important member of the operating room team, should be careful about pressure injuries that may develop during surgery, should regularly check the skin and prevent the risk, taking into account the individual risk factors of the patient.